Optimizing Renewable Energy Integration in the 3T Region: The Impact of Hybridization of PLTS-PLTD in Maratua on Emissions and Costs - Jemi Jemi; Andreas Prabowo; Richard Gamari Sobajian Rajagukguk (Interdisciplinary Social Studies, 2026)
Maratua Island in East Kalimantan is exploring the adoption of hybrid Solar Photovoltaic (PV) systems to support Indonesia's goal of achieving Net Zero Emission (NZE) by 2060. The island has long depended on diesel power plants (PLTD), resulting in high carbon emissions and operational costs. This study assesses the technical and operational feasibility of integrating a 300 kWp PV system with the existing diesel generator. Simulations using HOMER Pro show that the hybrid system significantly improves efficiency. The diesel generator, which currently consumes around 500 liters of fuel daily for a peak load of 499 kW, will reduce fuel consumption by over 70%, dropping to about 150 liters per day. CO? emissions will also decrease from 1.446 tons/year to 0.425 tons/year. Additionally, the levelized cost of electricity (LCOE) decreases from IDR 5,500/kWh to IDR 3,200/kWh. These findings suggest that hybrid PV systems are a cost-effective and sustainable energy solution for remote island regions, reducing fossil fuel reliance and carbon emissions.